Cluster diagrams with pvclust ggraph and ggplot2 - Kindt, R. (2020)
The main objective of this document is to show a pathway of generating dendrograms via the ggraph package for results that were obtained via pvclust. I expect that similar pathways can be used to generate dendrograms with ggraph.